Effect of Evaporator Outflow Rate on Air Distribution in the Computer Laboratory using CFD - Permatasari, Rosyida; Bambang Susetyarto, Martinus (International Journal of Electrical, Energy and Power System Engineering, 2020)
The ideal room temperature will create comfort in the learning and teaching process. With increasing outdoor air temperature due to climate change, an air conditioner is needed to reach the ideal room temperature. An air conditioner is an air conditioner that is needed to regulate the temperature and humidity of the air in a room. The purpose of this study is to determine the airflow pattern produced by air conditioning equipment and to determine the distribution of air temperature in the computer laboratory room. Computational Fluid Dynamic (CFD) is a simulation method used by using the ANSYS application. Based on research conducted in a computer laboratory room which has a length of 12 m, a width of 12 m, a chamfer of 3.93 m and a height of 3 m, the airflow pattern produced by the air conditioner is relatively the same between the variable air velocity 2.5 m / s and 3 m / s. Where the air will move straight in accordance with the outlet shape of the air conditioner and then experience a decrease in speed over a certain distance and a change in the direction of air flow occurs due to exposure to room properties and eventually spreads throughout the room. The average temperature in the computer laboratory room for the variable air velocity 2.5 m/s is 24 ° C. Meanwhile, the variable air velocity 3 m/s 23 ° C.